Modification of Access Policies for the Poverty Reduction and Growth Facility and the Exogenous Shocks Facility. (Policy Papers; Policy Paper ;, 2009)
The paper proposes a doubling of access limits on concessional lending to ensure that the Fund can respond effectively to the needs of low-income countries (LICs) severely affected by the current world economic downturn. Pending adoption of broader reforms to the LIC facilities architecture, higher access limits under the Poverty Reduction and Growth Facility (PRGF) and Exogenous Shocks Facility-High-Access Component (ESF-HAC) would give the Fund greater flexibility in assisting LICs, which have become more exposed to global volatility over time. A doubling of access limits would restore them to their 1998 levels in percent of GDP and would be consistent with the approach taken in determining new access limits for General Resources Account (GRA) resources. It would also be in line with the projected doubling of medium-term demand for concessional resources.